CONSEQUENCES OF RELATIONSHIP MARKETING ON CUSTOMER LOYALTY - Malik, Muhammad Shaukat; Ali, Huma; Ibraheem, Tahir (International Journal of Research -GRANTHAALAYAH, 2017)
The objective of present study is to investigate the consequences of relationship marketing on customer loyalty. The study also investigates the moderating role of customer expertise between relationship marketing and customer loyalty. The data used in the present study was collected by using a self – administered questionnaire. Data were collected from telecom industry of Pakistan; more specifically data source is the telecom users in Multan. Sample size is 500 and these questionnaires were distributed to collect data among top universities located in Multan. Out of 400 received questionnaires 330 were selected for analysis. SPSS (version 20.0) was used for analysis and statistical tools like ANOVA, correlation analysis and multiple regressions were used. The result of the present study show that there exists a direct relation between relationship marketing and customer loyalty as well as customer expertise moderates the relationship.